Fabrication of Laser Detectors using Ge wafer Doped with Sb - Al-Dhan, Ziad T; Al-Dabagh, Samar Y; Al-Hakeem, Thalfaa R (Al-Nahrain Journal of Science, 2016)
Germanium antimony (Ge:Sb) thin films have been fabricated by thermal evaporation system deposition at atmospheric pressure between (5.8x10-6 to 7.5x10-6) mbar. The (Ge:Sb) thin films then exposure to Nd:YAG laser with 1064μm wavelength at different energy densities (100,200) mj/cm2. XRD analysis show that Germanium antimony thin films are polycrystalline and the full width at half maximum (FWHM) increase as laser energy densities increases. Photocurrent and quantum efficiency of the detector increases as the laser energy densities increases.